SIMULASI PENETRASI PLTS ATAP YAYASAN TUNAS MANUNGGAL KAPASITAS 107 KWP KE GRID PLN 20 KV - Nurul Huda, Deni; Gunawan (Elektrika, 2025)
Along with changes in PLN regulations, the demand for rooftop solar PV (PLTS) permit applications under on-grid systems has increased due to the decreasing cost of equipment. Yayasan Tunas Manunggal has installed a 107 kWp rooftop solar PV system with a contractual power of 865 kVA supplied from PLN Substation PJ096. One of the main challenges of renewable energy is intermittency due to the characteristics of its primary energy source, where solar PV depends on sunlight intensity. The load pattern also significantly affects the PV system’s ability to supply loads to meet its contractual targets. This study aims to evaluate the power quality and reliability of electricity supply during weekly load dynamics. The method involves analyzing the load trend variations during weekdays and weekends, which critically affect the power factor, harmonics, and power flow direction. The results show that during weekday conditions, no reverse power occurs, and the grid quality remains stable. During weekend conditions, reverse power flow to the PLN grid occurs between 07:22 and 15:07, with the highest reverse power recorded at 65.540 watts at 12:28. The occurrence of reverse power flow to the PLN grid led to a notable increase in current Total Harmonic Distortion (THD-I), rising from an average value of 19.88% (recorded during holidays) to 31.11%. In contrast, other power quality parameters, such as voltage magnitude and voltage THD, remained within acceptable limits as per the relevant standards and were not significantly impacted.                                                                                                 Keywords: solar PV, load profile, reverse power. ABSTRAKSeiring perubahan regulasi PLN minat pengajuan ijin PLTS Atap dengan system On Grid cukup banyak karena biaya perangkat yang semakin murah. Yayasan Tunas Manunggal  memiliki 107 KWp daya kontrak ke PLN sebesar 865 KVA yang di suplai dari Gardu PLN PJ096. Problem utama energi terbarukan adalah intermittensi karena karakteristik sumber energi primernya, dimana PLTS dihadapkan pada intensitas penyinaran matahari. Pola pembebanan juga memiliki kontribusi pada kemampuan PLTS mensuplai beban untuk memenuhi target kontraknya. Penelitian ini bertujuan untuk mengevaluasi kualitas dan keandalan penyaluran tenaga listrik saat terjadi dinamikan beban mingguan. Metode yang digunakan membaca trend perubahan beban saat weekday dan weekend dimana merupakan faktor krusial yang mempengaruhi faktor daya, harmonic dan arah aliran daya. Hasil penelitian menunjukkan bahwa pada kondisi berbeban (weekday) tidak terjadi reverse power dan kualitas jaringan dalam keadaan baik. Saat  kondisi  tanpa beban (weekend), terjadi reverse power ke jaringan PLN mulai jam 07.22 sampai dengan jam 15.07 dengan nilai paling tinggi sebesar 65.540 watt pada jam 12.28. Reverse power ke jaringan PLN  menyebabkan peningkatan Total Harmonic Distortion arus (THD I) dari THD rata- rata ketika hari libur sebesar 19.88% menjadi 31.11 %. Untuk parameter lainnya seperti tegangan, dan THD tegangan masih dalam batas normal sesuai standar (tidak terganggu).
Keywords: PLTS atap; Load profile; reverse power